The Influence of Financial Literacy and Lifestyle on the Financial Management of Paulus Christian University of Indonesia 2021 Management Program Students - Kaya, Glein Putri; Golda, Cipta (Journal of Marketing Management and Innovative Business Review, 2024)
The aim of this research is to determine the influence of financial literacy and lifestyle on financial management among students of the Department of Management, Faculty of Economics and Business, Paulus Indonesian Christian University Class of 2021. The type of data used in this research is quantitative data originating from primary data originating from from the questionnaire given to management study program students class of 2021. In connection with the results of researching hypothesis testing by partial means variable X1 (financial literacy) with a value of 0.001<0.05 can be used to show that it has a significant influence on variable Y (financial management ), while variable X2 (lifestyle) with a value of 0.020>0.05 has no significant effect on variable Y (financial management). Thus, it can be stated that literature has an impact on the financial status of the Economics and Business Department faculty at Paulus Indonesian Christian University Class of 2021 .